Pregnancy following Mustard or Senning correction of transposition of the great arteries: a retrospective study. (3rd July 2015) - Cataldo, S; Doohan, M; Rice, K; Trinder, J; Stuart, AG; Curtis, SL
Abstract : Objective: To determine pregnancy outcome in women with atrial switch repair for transposition of the great arteries (TGA) and to compare follow up with a control group of childless women with the same repair. Design: Retrospective cohort study. Setting: Tertiary care medical centre. Population: About 21 patients compared with 15 controls. Methods: Review of records from joint cardiac‐obstetric clinic 1993–2013. Main outcome measures: Occurrence of cardiovascular events: maternal death, heart failure, arrhythmia, thromboembolic events, worsening systemic ventricular function, worsening tricuspid valve regurgitation and newly detected baffle problems. Results: There were 34 pregnancies in 21 women. Mean follow up was 100 months. No deaths or recurrence occurred. Events (few arrhythmias, thromboembolic events and baffle issues) were common in both groups: 13 (62%) patients and eight (53%) controls ( P  =   0.736). Worsening of ventricular function was similar in both groups: six (29%) patients and four (27%) controls ( P =  0.899). Worsening tricuspid regurgitation was more common in patients [11 (52%)] than controls (0)] ( P  < 0.001). Labour was induced in 76% cases: 32% for cardiac deterioration, 37% to control timing of delivery, and 26% for intrauterine growth restriction. Delivery was vaginal in 84% cases. Median gestational age was 37 (30–40) weeks, median birthweight 2525 g (1460–3530). In all, 38% babies were premature and 38% were small‐for‐gestational‐age. Conclusions: Cardiac events after atrial repair for TGA are equally common in pregnant women and non‐pregnant controls, although worsening tricuspid regurgitation occurs more frequently in pregnancy. Induction of labour is to be expected but vaginal delivery is achievable in most cases. Infants are likely to be premature and small‐for‐gestational‐age. Tweetable abstract: Pregnancy in atrial repair for TGA: cardiac events similar to controls, prematurity and small babies likely. Tweetable abstract: Pregnancy in atrial repair for TGA: cardiac events similar to controls, prematurity and small babies likely.